Transition of Assessment Tools in Medical Education - Adhikari, Khushbu; Pokharel, Shailesh Mani (Journal of Universal College of Medical Sciences, 2018)
Medical education is on an advancement in recent years in Nepal. Our ultimate goal as a medical educationist is to produce a confident “Medical Graduate” who are capable to provide health care to the people belonging to different regions of our country. The curriculum for the medical program helps us achieve this goal. The effectiveness of the curriculum taught is assessed by various methods. There are two types of assessment namely formative and summative assessment. Of the various competencies expected out of an undergraduate only few are assessed in the routine internal and summative assessment examinations. The first and second generation tools such as viva voce and structured essay type questions evaluate the clinical reasoning without addressing other competencies such as social skills. The inadequacy in these assessment methods can hinder our way to achieving our goal. Social skills like communication skills, attitude, professionalism, leadership qualities, and skills of healing patients rather than just treating the disease is to be emphasized and addressed. Hence, third generation assessment like 360 degree assessment, experiential assessment, and portfolio can help us achieve our goal of creating efficient medical graduates which incorporates assessment of social skills as well.